Revitalisasi koleksi perpustakaan vokasi melalui penyiangan sistematis dan stock opname - Noviandri Talcha Anjani (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2026)
Maintaining the relevance and quality of collections in a vocational library is critical given the rapid evolution of industry standards. This study describes the systematic collection revitalization process at the Poltekpar NHI Bandung Library, carried out through weeding and stock-taking activities. Using a descriptive-qualitative approach based on an intensive 40-day Program Penguatan Pengalaman Profesional Non-Kependidikan (P3NK), the revitalization followed strict criteria, including physical condition, usage frequency, and a 10-year currency rule, to ensure alignment with the needs of the tourism and hospitality industry. The weeding process identified 612 copies for removal, with the highest concentration in the 600 class (applied sciences). Following the wedding, a comprehensive stock opname revealed a physical count of 14,479 copies. Data synchronization between physical findings and the integrated library database (website) identified a discrepancy of 615 copies. Challenges such as technical inaccuracies in security systems and suboptimal procurement processes influenced the decision-making during the weeding stage. This study underscores that systematic collection maintenance is essential for vocational libraries to provide up-to-date resources and improve overall service efficiency.